“Overcoming the Defect”: Congenital Anomalies in 6984 Consecutive Deliveries in a Tertiary Care Center in Nepal - Aryal, Shreyashi; Shrestha, Deepak (Journal of Lumbini Medical College, 2020)
Introduction: Neonatal congenital anomalies are the 17th leading cause of global disease burden. Congenital anomalies in low-income countries are high due to prevalence of nutritional deficiencies, intrauterine infections, teratogenic exposure and unsupervised self medication. This study aimed to find various antenatal risk factors for birth defects and the delays in health seeking behaviors in cases of still births with birth defects.Methods: In this retrospective study the records of mothers and neonates born with congenital anomalies during the period of 30 months were reviewed. Consanguinity, intrauterine infections, presence of anemia, and history of drug intake were noted. In cases of stillborns with anomalies, mode of delivery, labor complications and the three delays leading to morbidities were also noted.Results: There were 65 congenital anomalies during the study period with an incidence of 9.3 per 1000 births. Out of them, 43 were live births and 22 were still births. The commonest anomaly amongst live births was of musculoskeletal system (n=11, 25.5%) and amongst still births was of nervous system (n=10, 45.4%). Consanguineous marriage was present in 30 (46.1%) parents and folic acid was taken by only 26(40%) of the mothers. In cases of still births with anomalies, most deliveries were vaginal (97%) without any maternal complications. Among the three delays, delay in deciding to seek care was observed in most cases (n=14, 63.6%).Conclusion: Factors like consanguinity and intake of folic acid are modifiable factors useful in preventing congenital anomalies. Encouraging early antenatal visits might help in early detection of anomalies.